MANAGEMENT CONTROL SYSTEMS IN ESG-BASED GOVERNANCE: MAPPING RESEARCH STREAMS AND FUTURE DIRECTIONS. - Halimahtussakdiah, Halimahtussakdiah; Wahyuningsih, Eny (Universitas Riau, 2026)
This study maps existing research streams and future directions on Management Control Systems (MCS) and Environmental, Social, and Governance (ESG). Using a bibliometric approach, 319 Scopus-indexed journal articles were analyzed with VOSviewer. Bibliographic coupling and co-word analysis were employed to examine the knowledge structure, dominant themes, and research gaps within the MCS–ESG literature.The findings show that prior research predominantly emphasizes integrative frameworks and implementation strategies that position MCS as a mechanism for supporting ESG objectives, particularly through performance measurement, strategic decision-making, and accountability systems. Four major research clusters emerge, illustrating the evolving role of MCS in sustainability governance. The analysis also highlights promising avenues for future studies, including digital transformation, sustainability accounting innovation, and the strategic integration of MCS to enhance ESG performance across sectors.This study contributes by explicitly framing MCS as a governance mechanism rather than merely a reporting tool. It provides a conceptual roadmap for scholars and offers practical insights for managers, system designers, and policymakers seeking to align ESG objectives with control systems to advance sustainable development.